2016
DOI: 10.1016/j.marpolbul.2016.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Barcodes of marine invertebrates from north Iberian ports: Native diversity and resistance to biological invasions

Abstract: Ports are gateways for many marine organisms transported by ships worldwide, especially non-indigenous species (NIS). In this study carried out in North Iberian ports (Cantabrian Sea, Bay of Biscay) we have observed 38% of exotic macroinvertebrates. Four species, namely the barnacle Austrominius modestus, the tubeworm Ficopomatus enigmaticus, the Pacific oyster Crassostrea gigas and the pygmy mussel Xenostrobus securis, exhibited clear signs of invasiveness. A total of 671 barcode (cytochrome oxidase subunit I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 38 publications
(46 reference statements)
4
59
1
1
Order By: Relevance
“…The current Spanish invasive species catalogue (BOE, 2013) includes only one (Crepidula) of the exotic genera found in these estuaries using NGS and metabarcoding. This motivated a specific postsampling strategy for detecting Crepidula spp.in Asturias with more intense scrutiny of the Villaviciosa estuary, where C. fornicata had not been previously described (Miralles et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The current Spanish invasive species catalogue (BOE, 2013) includes only one (Crepidula) of the exotic genera found in these estuaries using NGS and metabarcoding. This motivated a specific postsampling strategy for detecting Crepidula spp.in Asturias with more intense scrutiny of the Villaviciosa estuary, where C. fornicata had not been previously described (Miralles et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…From 1998 to 2009, it was found in the four Rías Baixas and in the Ría del Ferrol in Galicia (Rolán & Trigo, 2007;Besteiro, Urgorri, Moreira, & Díaz-Agras, 2009). In Asturias, there was one previous report, without any genetic assessment, of C. fornicata in the Eo estuary (Arias, Richter & Anadón, 2012) and one piece of genetic evidence of the species in Figueras Port in the same estuary in 2016 (Miralles et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the invasive species Crepidula fornicata almost destroyed the oyster farms in Brittany [ 5 ]. Ports and marinas are perhaps the keystones in maritime biosecurity [ 6 , 7 , 8 , 9 , 10 ]. They are hubs of maritime traffic where vessels of all the continents stop for days or months.…”
Section: Introductionmentioning
confidence: 99%
“…This is important because it is still unclear if A. verticillata is a widespread species or a complex of cryptic species (Nascimento 2015, Waeschenbach et al 2015. To date, only few studies (Nascimento 2015, Waeschenbach et al 2015, Miralles et al 2016, Santos et al 2017 have confirmed the identity of the bryozoan from 6 countries (Australia, Brazil, Italy, Mexico, Spain, and the USA) using molecular analyses. Applying this type of approach to Mexican specimens will not only allow a more accurate identification, but also give evidence on the introduction and dispersal of this species in the country.…”
Section: Discussionmentioning
confidence: 99%